Association of clinical factors with thrombocytopenia in patients receiving linezolid treatment: a retrospective study - Thi Phuong Thao, Le; Duc Trung, Nguyen; Thi My, Le; Minh Hong, Le; Viet Hoan, Bui; Quang Hung, Vu; Dang Hai, Pham (The Journal of Infection in Developing Countries, 2024)
Introduction: Linezolid (LZD) plays an important role in the treatment of severe infections caused by Gram-positive bacteria. Thrombocytopenia is regarded as one of the most common side effects of linezolid, which results from the destruction of platelets or myelosuppression. The study aimed to identify the risk factors associated with the development of thrombocytopenia in Vietnamese patients. Methodology: This retrospective, descriptive cross-sectional study was performed on adult patients who received parenteral LZD therapy (1,200 mg/day) in at least 3 days between January 2020 and June 2021 at a tertiary referral hospital in Vietnam. Thrombocytopenia was defined as either a final platelet count of less than 100 G/L or a 25% decrease in platelet count from baseline. Multivariate logistic regression analysis was applied to predict risk factors associated with LZD-induced thrombocytopenia. Results: In the 208 patients included in the study, the average age was 69 and males accounted for 73.1%. LZD-induced thrombocytopenia occurred in 37% of patients. LZD-induced thrombocytopenia was significantly associated with shock (HR = 8.26, 95% CI 3.82 – 17.84, p < 0.001), baseline creatinine clearance (HR = 1.02, 95% CI [1.01 – 1.03], p = 0.002), and duration of LZD treatment of at least 14 days (HR = 4.45, 95% CI [1.83 – 11.05], p = 0.001). Conclusions: The results showed that thrombocytopenia was fairly common in patients using linezolid. Shock, renal failure, and duration of linezolid therapy of at least 14 days were significant risk factors for the incidence of linezolid-induced thrombocytopenia.